Thinking and Working Politically in the Land Sector in Mekong Region - Burns, Tony; Ingalls, Micah; Rickersey, Kate
In recent decades, the World Bank and many bilateral development partn ers have provided funding to support land administration reform. Tradi tional land administration reform projects focus on the economic and t echnical design of interventions based on a library of best practice, commonly avoiding the “messy politics” typically involved in land gove rnance. Experience and lessons from land administration reform initiat ives have been documented and a recurrent theme is that many projects fail to create effective, transformative change and gain the critical mass, and the community participation, necessary to ensure the sustain ability of land administration reform. Over the last decade there have been concerted efforts to develop more politically informed ways of t hinking and working using a range of methodologies referred to, variou sly, as Thinking and Working Politicallyi (TWP), Problem Driven Iterat ive Adaptation (PDIA) and Doing Development Differently (DDD). There i s little evidence that these different approaches have been applied in the land sector.